Methodologies for Digital Profiling of Foreign Partners to Assess Their Reliability and Solvency - Pankulych, Ivan (Академічні візії, 2026)
Relevance of the study is determined by the increasing instability of the international economic environment, the intensification of cross-border financial, reputational, and regulatory risks, and the limited effectiveness of traditional approaches to assessing the reliability and solvency of foreign partners. The ongoing digitalization of business processes and the expansion of available data sources necessitate the development of scientifically grounded digital profiling methodologies as tools for improving the quality of managerial decision-making in foreign economic activity. The purpose of the article is to substantiate and systematize methodological approaches to the digital profiling of foreign partners in order to ensure a comprehensive assessment of their reliability and solvency under conditions of heightened instability in the international economic environment. Research methods include analytical generalization of contemporary practices in foreign economic risk management, systematization of digital data and information sources used in partner profiling, analytical review of digital analysis methods and data analytics tools, as well as logical and structural analysis of scientific and practical challenges associated with the application of digital profiling methodologies. The results of the study demonstrate that digital profiling functions as an integrated analytical instrument for evaluating both financial stability and behavioral patterns of foreign counterparties. Key types of digital data and information sources forming a partner’s digital profile are investigated, and the main methods of digital analysis used to construct reliability and solvency assessment models are characterized. It is identified that the effectiveness of digital profiling is constrained by data fragmentation, algorithmic bias risks, legal and regulatory limitations, and restricted interpretability of complex analytical models. Conclusions indicate that the integration of digital profiling methodologies into enterprise risk management systems is justified and enables a transition from static, one-time counterparty verification to continuous analytical monitoring, thereby increasing the validity of managerial decisions and reducing partnership risks in foreign economic activity. Prospects for further research are associated with the development of interpretable digital profiling models, improvement of heterogeneous data integration methods, and empirical validation of the proposed approaches across different sectors of international economic activity.